2020
DOI: 10.1186/s12981-020-00323-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age on CD4 recovery and viral suppression over time among adults living with HIV who initiated antiretroviral therapy in the African Cohort Study

Abstract: Introduction With increased use of antiretroviral therapy (ART), HIV mortality rates are declining and people living with HIV (PLWH) are surviving longer. We characterized CD4 recovery and viral suppression among adults aged < 50 and ≥ 50 years living with HIV who initiated ART in the African Cohort Study (AFRICOS). Methods Beginning in January 2013, PLWH at twelve clinics in Kenya, Uganda, Tanzania and Nigeria underwent medical history review, CD4 and viral load testing as part of the ongoing African Coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
3
10
1
Order By: Relevance
“…Thirty‐nine studies reported on initiation of ART [2,21,23,28,33,34,37,40‐42,44‐47,49‐54,23,55‐62,64,66,67‐75], with 25 (64%) defining numerators and denominators. Thirty‐two were longitudinal, four of mixed design and three were cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty‐nine studies reported on initiation of ART [2,21,23,28,33,34,37,40‐42,44‐47,49‐54,23,55‐62,64,66,67‐75], with 25 (64%) defining numerators and denominators. Thirty‐two were longitudinal, four of mixed design and three were cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 52 studies reported numbers or percentages of patients retained at this step [8,20‐32,34,36,40‐43,46,56,58,65,68,69,72‐74,76‐93,95‐99]. The majority of studies (32 studies, 62%) covering this step were longitudinal studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations